Lung involvement is a risk factor for treatment resistance in patients with polymyositis and dermatomyositis - Elif Altunel Kılınç,; Bengisu Ece Duman,; Süleyman Özbek, (Archives of Rheumatology, 2025)
Objectives: This study aimed to investigate the factors that lead to treatment change in patients with polymyositis (PM) and dermatomyositis (DM) and to present its contribution to our clinical approach. Patients and methods: A retrospective analysis was conducted on 141 patients (103 females, 38 males; mean age: 51.2±14.3 years; range, 22 to 74 years) diagnosed with PM (n=87; 61 females, 26 males; mean age: 50.2±13.4 years; range, 22 to 74 years) or DM (n=54; 42 females, 12 males; mean age: 52.7±15.8 years; range, 22 to 72 years) between January 2003 and May 2024. Patients were evaluated for treatment changes, reasons for these changes, and disease characteristics, including disease duration, creatine kinase, erythrocyte sedimentation rate, and C-reactive protein levels. Results: Treatment changes were observed in 86 (60.9%) patients, comprising 58 (67%) PM and 28 (33%) DM cases. The primary reasons for treatment modification included drug intolerance in nine (10.5%) patients and uncontrolled disease in 77 (89.5%) patients. Among the uncontrolled patients, 34 (44.7%) exhibited lung involvement, 16 (21%) had peripheral joint involvement, one (1.3%) cardiac involvement, and 26 (34.3%) showed increased muscular symptoms. Statistical analysis revealed that lung involvement was an independent risk factor influencing the necessity for medication changes, while other analyzed factors exhibited no significant impact. Conclusion: The findings underscore the critical role of lung involvement in the management of PM and DM, highlighting the need for heightened awareness of respiratory symptoms in these patients. These results provide valuable insights for clinical practice, emphasizing the importance of individualized treatment strategies in managing PM and DM patients.